The importance of youth and adult education: An analysis of youth and adult illiteracy in Brazil - Siqueira, João Victor (2023)
Faced with our Brazilian reality and the social discrepancy we experience in education, Youth and Adult Teaching becomes a solution to try to solve this inequality, however, in practice, teachers within the classroom end up strengthening school segregation beyond spatial segregation . There is still a lot to advance in relation to the teaching of Youth and Adult Education - EJA, since it is increasingly undervalued and it is not a policy with many investments. In this sense, this article seeks to contextualize illiteracy in Brazil with data and the importance of the EJA modality in an attempt to solve and alleviate the educational inequality that we live in Brazil today, using data collected from the IBGE and experience reports in the teaching modality in question.